Emergence of the CD226 Axis in Cancer Immunotherapy - Conner, Michael; Hance, Ken W.; Yadavilli, Sapna; Smothers, James; Waight, Jeremy D. (Frontiers in Immunology, 2022)
In recent years, a set of immune receptors that interact with members of the nectin/nectin-like (necl) family has garnered significant attention as possible points of manipulation in cancer. Central to this axis, CD226, TIGIT, and CD96 represent ligand (CD155)-competitive co-stimulatory/inhibitory receptors, analogous to the CTLA-4/B7/CD28 tripartite. The identification of PVRIG (CD112R) and CD112 has introduced complexity and enabled additional nodes of therapeutic intervention. By virtue of the clinical progression of TIGIT antagonists and emergence of novel CD96- and PVRIG-based approaches, our overall understanding of the ‘CD226 axis’ in cancer immunotherapy is starting to take shape. However, several questions remain regarding the unique characteristics of, and mechanistic interplay between, each receptor-ligand pair. This review provides an overview of the CD226 axis in the context of cancer, with a focus on the status of immunotherapeutic strategies (TIGIT, CD96, and PVRIG) and their underlying biology (i.e., cis/trans interactions). We also integrate our emerging knowledge of the immune populations involved, key considerations for Fc gamma (γ) receptor biology in therapeutic activity, and a snapshot of the rapidly evolving clinical landscape.